EVENT AND EVOLUTION. - Parisi, Luciana (Southern Journal of Philosophy)
Why have theories of evolution become now (and again) a matter of concern for critically rethinking sex and sexual difference? Why after years of deconstructing the ontologies of sex rooted in biological discourses and metaphysics of identity has critical thought turned to biology, physics, and mathematics? One way to tackle this new turn toward scientific thought may be derived from the reaction against an overused method of textual critique, which has come short of engaging with the reality of matter. If sexuality and sex are material forms of irreducible difference, then one needs a window into the material processes that lead to such forms.